2016
DOI: 10.1016/j.jped.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malnutrition on cardiac autonomic modulation in children

Abstract: Malnourished children present changes in cardiac autonomic modulation, characterized by reductions in both sympathetic and parasympathetic activity, as well as increased heart rate and decreased blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
8
0
4
Order By: Relevance
“…As limitations of this study, we can highlight the restricted sample size and absence of analysis of other variables that may be related to the clinical evolution and ANS in preterm infants, such as the presence of neurological lesions or the occurrence of low weight and malnutrition [28, 32]. As an additional limitation, we see the lack of long-term follow-up, is the lack of published data with which to compare our results.…”
Section: Discussionmentioning
confidence: 93%
“…As limitations of this study, we can highlight the restricted sample size and absence of analysis of other variables that may be related to the clinical evolution and ANS in preterm infants, such as the presence of neurological lesions or the occurrence of low weight and malnutrition [28, 32]. As an additional limitation, we see the lack of long-term follow-up, is the lack of published data with which to compare our results.…”
Section: Discussionmentioning
confidence: 93%
“…Para mais, em outro estudo realizado com 70 crianças desnutridas, observou-se diminuição tanto do tônus simpático como do parassimpático (BF=343,43 ± 259,06; AF= 208,69 ± 176,01; BF/AF=2,33 ± 1,67; SDNN=32,09 ± 11,16; RMSSD= 21,54 ± 9,48; pNN50= 5,35 ± 6.62), bem como, da pressão arterial sistólica e diastólica, com elevação da FC de repouso. Essas adaptações foram atribuídas ao quadro de desnutrição apresentado pelos participantes do estudo [7], o que torna fortemente sugestivo que o quadro de desnutrição e caquexia, comumente apresentado por pessoas com PC, possa influenciar na atividade simpato-vagal destes indivíduos.…”
Section: Discussionunclassified
“…This type of approach could provide inputs for understanding stress levels through the assessment of facial patterns [44,45]. With regard to ECG data, studies [46][47][48] have demonstrated that this noninvasive biomarker can be used to measure malnutrition, in addition to the use of some specific standards for proxies related to temperature increase. The data from the proximity sensors indicated that nudges sent via SMS text messaging played a role in activating behavior change, and despite being an observation not yet reported in the literature, a similar approach used in Africa showed promising results for social network pattern studies [49].…”
Section: Comparison With Prior Workmentioning
confidence: 99%